2020
DOI: 10.3329/bhj.v35i1.49147
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Massive Metoprolol Overdose Successfully Managed

Abstract: Not Available Bangladesh Heart Journal 2020; 35(1) : 71-73

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…It has moderate lipid solubility and blocks β1 adrenergic receptors. It is reported that the threshold value is 400 mg in adults and 5mg/kg in children (9). Metoprolol overdose, depending on the dose taken in the clinic, may lead to symptoms such as bradycardia, hypotension, cardiogenic shock, hypoglycemia, hypothermia, seizure, altered consciousness, QT prolongation and QRS enlargement (10).…”
Section: Figure 1 Drug Particles Visible In the Stomach Lumen On The Patient's Abdominal Tomographymentioning
confidence: 99%
See 3 more Smart Citations
“…It has moderate lipid solubility and blocks β1 adrenergic receptors. It is reported that the threshold value is 400 mg in adults and 5mg/kg in children (9). Metoprolol overdose, depending on the dose taken in the clinic, may lead to symptoms such as bradycardia, hypotension, cardiogenic shock, hypoglycemia, hypothermia, seizure, altered consciousness, QT prolongation and QRS enlargement (10).…”
Section: Figure 1 Drug Particles Visible In the Stomach Lumen On The Patient's Abdominal Tomographymentioning
confidence: 99%
“…Due to its lipophilic properties, the drug crosses the bloodbrain barrier in β-blocker poisoning and central nervous system effects may be observed. Therefore, rapid airway management is important in such patients (9). In literature, majority of the publications recommend gastric lavage and the administration of activated charcoal in β-blocker poisoning (11,12).…”
Section: Figure 1 Drug Particles Visible In the Stomach Lumen On The Patient's Abdominal Tomographymentioning
confidence: 99%
See 2 more Smart Citations